Income Analysis and Feasibility of Farming Business with Rawit Chili Intercropping System in Rokan Hulu Regency - Andi Afrizal (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
The purpose of this study was to determine the income and to find out whether the Cayenne Chili Tumpangsari Farming Business was feasible to be cultivated in Rokan Hulu Regency. Data Analysis Techniques using both income analysis and farming feasibility analysis. The results showed that the total revenue achieved by cayenne pepper farmers was Rp. 81,640,000 with an average income of Rp. 69,449,550. And cayenne pepper intercropping in Rokan Hulu Regency is feasible to operate with an R/C value of 5, which means that each expenditure is Rp. 100 will get a receipt of Rp. 500.